Thalidomide as an effective treatment in a case of Osler Weber Rendu syndrome: a case report - Bandyopadhyay, Titli; Anand, VT; Gangopadhyay, Dibyendu (Asian Journal of Medical Sciences, 2016)
Osler Weber Rendu Syndrome (OWRS), or Hereditary Hemorrhagic telangiectasia (HHT) is an autosomal dominant disease presents with epistaxis, telangiactesia and multiorgan vascular dysplasia. Recurrent epistaxis is common in these patients and various local forms of therapy is tried to treat the condition, but there is lack of definitive and effective treatment. We present a patient of HHT with severe recurrent epistaxis successfully treated with thalidomide. Asian Journal of Medical Sciences Vol.7(4) 2016 107-109